1994
DOI: 10.1177/019262339402200304
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Observation of Spontaneous Endometrial Adenocarcinoma Development in Donryu Rats

Abstract: Sequential observation of spontaneous endometrial adenocarcinoma development revealed a clear, hormone-dependent, histogenetic pathway in Donryu rats. The first histological changes of the uterine endometrium appeared in both the lining epithelium and uterine gland of the endometrium at 6 mo of age, along with the beginning of persistent estrus. These changes included areas of tall columnar epithelium and gland formation in the lining epithelium as well as metaplastic change in the uterine gland. At 8 mo of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 8 publications
5
55
0
Order By: Relevance
“…Studies that have been cited in support of the proposed mode of action for D5 carcinogenicity include studies that compare spontaneous uterine endometrial tumor incidences and E/P ratios in Donyru and F344 rats. The Donryu rats experienced substantially greater E/P ratios, endometrial hyperplasia and spontaneous uterine endometrial tumor incidences compared to the F344 rats (Nagaoka et al, 1990(Nagaoka et al, , 1994Ando-Lu et al, 1998). These studies have been cited as evidence for the proposed D5 carcinogenicity mode of action; that is, D5 dopamine agonist activity causes a decrease in PRL release, leading to an increased E/P ratio which results in increased endometrial hyperplasia, and thence endometrial tumors.…”
Section: D5 Cancer Risk Evaluationmentioning
confidence: 94%
“…Studies that have been cited in support of the proposed mode of action for D5 carcinogenicity include studies that compare spontaneous uterine endometrial tumor incidences and E/P ratios in Donyru and F344 rats. The Donryu rats experienced substantially greater E/P ratios, endometrial hyperplasia and spontaneous uterine endometrial tumor incidences compared to the F344 rats (Nagaoka et al, 1990(Nagaoka et al, , 1994Ando-Lu et al, 1998). These studies have been cited as evidence for the proposed D5 carcinogenicity mode of action; that is, D5 dopamine agonist activity causes a decrease in PRL release, leading to an increased E/P ratio which results in increased endometrial hyperplasia, and thence endometrial tumors.…”
Section: D5 Cancer Risk Evaluationmentioning
confidence: 94%
“…These tissues and the pituitary, thymus, mammary gland, brain, vagina, b o n e w i t h b o n e m a r r o w a n d m a c ro s c o p i c abnormalities were fixed and routinely processed for histopathological examination. The upper, middle and lower parts of each uterine horn and the uterine cervix were cross-sectionally cut into 3 pieces to evaluate uterine neoplastic lesions, and classified into three degrees of atypical hyperplasia (slight, moderate, or severe) and adenocarcinomas, according to criteria described previously [11][12][13]. In addition, adenocarcinomas were subdivided into well, moderately and poorly differentiated types, and also classified as to the degree of invasion: limited to the uterus, invading into the serosa and/ or surrounding adnexae, and with distant metastasis, in accordance with the simplified FIGO histopathological grades for human uterine cancers [15].…”
Section: Uterine Carcinogenesis and Histopathological Examinationmentioning
confidence: 99%
“…In rats, naturally occurring endometrial adenocarcinomas are rare, but Maekawa et al found a high incidence of such lesions with morphological and biological similarities to human tumors in aged animals of the Donryu strain [10]. They further demonstrated that endometrial adenocarcinoma development was remarkably linked to an age related ovarian hormonal imbalance that resulted in an increase in the serum estrogen/progesterone ratio [11,12]. Using this rat strain, they have also established a 2-stage uterine carcinogenesis model to detect promoting or preventive effects of test-chemicals [13,14].…”
mentioning
confidence: 99%
“…Uterine proliferative lesions were classified into adenocarcinoma and hyperplasia categories, according to our criteria reported previously. 14) Mammary, pituitary and adrenal proliferative lesions were diagnosed according to the criteria described in "Pathology of the Fischer Rat" edited by Boorman et al 16) Statistical analysis Data concerning the incidences of the lesions, survival rates and persistent estrous rates were statistically analyzed using the one-sided Fisher's exact probability test or χ 2 test. Other data were analyzed using Student's t test.…”
Section: Animalsmentioning
confidence: 99%
“…12) This rat strain yields spontaneous endometrial adenocarcinomas at high incidence, and hormonal imbalance, particularly an age-related increase of the estrogen:progesterone (E 2 :P) ratio may play an important causative role. 13,14) Thus, the Donryu rat strain has been considered as a good animal model for human endometrial adenocarcinomas caused by endogenous estrogens, as reviewed quite recently. 15) High yields of spontaneous mammary tumors are also observed in females of this rat strain.…”
mentioning
confidence: 99%